The Analysis of Work Engagement and Self Efficacy Towards The Self-Development of Tourism Entrepreneur In Labuan Bajo and Timor Is-land - Ni Putu Nursiani Nursiani; Rolland E. Fanggidae; Debryana Yoga Salean; Merlyn Kurniawati; Jachielin H. Lada (Green Publisher Indonesia, 2023)
East Nusa Tenggara is a province that has great natural wealth and tourism potential. The enthusiasm tourists to visit tourist objects in NTT is quite large, seen from the increase in tourist visits every year. The current phenomenon of tourism turmoil in NTT creates many opportunities as well as threats to the sustainability the sustainable tourism industry in the future. A gap like this creates opportunities for human resources in tourism sector increase economic contribution to the region. One strategy that can be implemented is to encourage more business actors in the tourism sector and develop the self-capacity of business actors who already exist in the world of tourism. Apart from that, it is also important to increase the capacity and professionalism of human resources for tourism and the creative economy, so that the competitiveness of tourism in NTT can also increase. In an effort to maximize the achievement these goals, human resources (HR) are needed who have the competence, knowledge, ability, productivity and good performance. Efforts to meet the objectives increasing the capacity and professionalism maximum tourism human resources involve self-efficacy and strong work involvement from within the business actors. This study aims to analyze Work Engagement and Self-Efficacy in Self-Development Business Actors in the Tourism Sector in NTT. The research was conducted by studying the phenomena and entrepreneurial behavior the tourism sector in Labuan Bajo (a tourist city with the highest tourist visit rate in NTT) and Timor Island (an area with the second highest tourist visit rate).